Test design and validity evidence of interactive speaking assessment in the era of emerging technologies. (January 2023) - Jung Youn, Soo
As access to smartphones and emerging technologies has become ubiquitous in our daily lives and in language learning, technology-mediated social interaction has become common in teaching and assessing L2 speaking. The changing ecology of L2 spoken interaction provides language educators and testers with opportunities for renewed test design and the gathering of context-sensitive validity evidence of interactive speaking assessment. First, I review the current research on interactive speaking assessment focusing on commonly used test formats and types of validity evidence. Second, I discuss recent research that reports the use of artificial intelligence and technologies in teaching and assessing speaking in order to understand how and what evidence of interactive speaking is elicited. Based on the discussion, I argue that it is critical to identify what features of interactive speaking are elicited depending on the types of technology-mediated interaction for valid assessment decisions in relation to intended uses. I further discuss opportunities and challenges for future research on test design and eliciting validity evidence of interactive speaking using technology-mediated interaction.